Efficacy of neoadjuvant therapy and lymph node dissection in advanced gallbladder cancer without distant metastases: a SEER database analysis - Dong, Jun; Zhu, Zhengqiu (Frontiers in Oncology, 2024)
PurposeTo investigate the effectiveness of neoadjuvant therapy and lymph node dissection(LND) on overall survival (OS) in patients with stage III/IV gallbladder cancer without distant metastases.MethodsData from 101 patients who received neoadjuvant therapy followed by surgery combined with adjuvant chemotherapy, and 1412 patients who received direct surgical treatment followed by adjuvant chemotherapy, were collected from the SEER database from 2004 to 2020. Patients were divided into group A (neoadjuvant therapy) and group B (direct surgery) based on the treatment modality. A total of 202 cases were obtained after propensity score matching, with 101 cases in each group (A and B). Cox unifactorial and multifactorial analyses were performed to identify independent risk factors for patients with advanced cholecystic carcinoma, and the Kaplan-Meier method was used to analyze overall survival (OS). The Cox proportional hazards model was used to investigate the effect of different subgroups on OS in both patient groups. Further survival analyses were conducted to determine whether lymph node dissection(LND) was beneficial for patients receiving neoadjuvant therapy for gallbladder cancer.ResultsCox univariate analysis showed that marital status, AJCC stage, number of LND, tumor size, and treatment modality were associated with OS (P<0.05). Cox multifactorial regression analysis indicated that AJCC stage, LND, tumor size, and treatment modality were independent risk factors for OS in patients with non-metastatic advanced gallbladder cancer (P<0.05). Survival curves demonstrated that the OS in group A was longer than in group B (median OS: 30 months vs. 14 months, P<0.001). Subgroup analysis indicated that neoadjuvant therapy had a consistent effect on the OS of patients with advanced gallbladder cancer, improving both survival time and outcomes. Survival curves indicated that lymph node dissection was not significant in group A patients (p>0.05) but was significant in group B (p<0.05).ConclusionNeoadjuvant therapy can improve the OS of patients with non-metastatic stage III/IV gallbladder cancer and is an independent risk factor affecting prognosis; however, the significance of lymph node dissection in these patients still needs further study.